Kentsel dönüşümün ötesinde: Foucault'nun sorunsallaştırma, nesneleştirme ve özneleştirme kavramları perspektifinden Türkiye'deki kentsel dönüşüm söylem oluşumuna bakış - Araşan, Ahmet (İstanbul Bilgi Üniversitesi, 2012)
[Abstract Not Available]
Beyond the urban transformation: a look into the formation of urban transformation from the perspective of Foucault's concepts of problematization, objectification and subjectification